MENINGKATKAN PEMAHAMAN SISWA TENTANG NILAI-NILAI AKHLAK MELALUI CERITA NABI DAN RASUL DI SD NEGERI 016 SIMANGAMBAT - Marlina; Idham Hasibuan, Rahmi Ramadhani, (CV. Alfa Pustaka, 2024)
This study aims to improve students' understanding of moral values ​​through the stories of the Prophets and Apostles at SD Negeri 016 Simangambat. The study was conducted in two cycles using the Classroom Action Research (CAR) approach in the odd semester of 2023-2024. The subjects of the study were 30 grade VI students. Data were collected through observation, interviews, comprehension tests, and teacher reflections. The results showed a significant increase in students' understanding of moral values ​​after learning using the stories of the Prophets and Apostles. The average student score on the initial test was 60, which increased by 41.6% to 85 on the test after cycle II. Observations showed that 90% of students were enthusiastic and active in learning, with 85% participating more often in discussions and telling lessons. In addition, around 75% of students showed more polite, patient, and respectful behavior. Interviews with students revealed that 80% found it easier to understand moral values ​​after listening to the stories of the Prophets and Apostles. Teachers noted that this story-based learning increased students' interest and understanding of Islamic Religious Education. However, it is necessary to have more relevant story variations to the students’ social situations. Overall, this learning is effective in improving students’ understanding of moral values ​​and positive attitudes.